Development of multiple linear regression for particulate matter (PM10) forecasting during episodic transboundary haze event in Malaysia - Abdullah S.; Napi N.N.L.M.; Ahmed A.N.; Mansor W.N.W.; Mansor A.A.; Ismail M.; Abdullah A.M.; Ramly Z.T.A. (MDPI AG, 2023)
Air quality; Carbon monoxide; Errors; Forecasting; Linear regression; Nitrogen oxides; Sulfur dioxide; Wind; Accuracy; Forecasting modeling; Malaysia; Multiple linear regressions; Particulate Matter; Precautionary measures; Stepwise multiple linear regression; Trans-boundary; Particles (particulate matter); accuracy assessment; error analysis; forecasting method; haze; multiple regression; particulate matter; prediction; Malaysia